Methods and techniques applied to develop the speaking skills in english language on students of eight, minth and tenth grade of the general basic education of Nueve de Octubre Bachillearo high school in the city of Machala. 2014-2015 academic year. - Guamán Jiménez, Jéssica Margarita (2015)
This work focuses on students of eighth, ninth and tenth grade of General Basic Education Baccalaureate Nine of October 2014 - 2015 to achieve determine the methods and techniques used by teachers to develop oral production. Based on the classic, behavioral and obsolete and techniques currently employed teachers because of not having the proper training to use new teaching tools generating demotivation and lack of student participation.